2020
DOI: 10.1186/s12974-020-01908-z
|View full text |Cite
|
Sign up to set email alerts
|

Angiotensin AT1 and AT2 receptor heteromer expression in the hemilesioned rat model of Parkinson’s disease that increases with levodopa-induced dyskinesia

Abstract: Background/aims: The renin-angiotensin system (RAS) is altered in Parkinson's disease (PD), a disease due to substantia nigra neurodegeneration and whose dopamine-replacement therapy, using the precursor levodopa, leads to dyskinesias as the main side effect. Angiotensin AT 1 and AT 2 receptors, mainly known for their role in regulating water homeostasis and blood pressure and able to form heterodimers (AT 1/2 Hets), are present in the central nervous system. We assessed the functionality and expression of AT … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
31
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 20 publications
(32 citation statements)
references
References 65 publications
1
31
0
Order By: Relevance
“…AT 1 -β 2 AR heteromers have been described in several studies [ 9 , 24 , 25 ] and are involved in the mediation of cardiomyocyte contractility and heart rate in intact mice [ 24 ]. The pharmacology of the AT 1 -AT 2 heteromer has been extensively studied [ 4 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 ], and most recently, has been implicated in Parkinson’s disease [ 27 ].…”
Section: Introductionmentioning
confidence: 99%
“…AT 1 -β 2 AR heteromers have been described in several studies [ 9 , 24 , 25 ] and are involved in the mediation of cardiomyocyte contractility and heart rate in intact mice [ 24 ]. The pharmacology of the AT 1 -AT 2 heteromer has been extensively studied [ 4 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 ], and most recently, has been implicated in Parkinson’s disease [ 27 ].…”
Section: Introductionmentioning
confidence: 99%
“…Heteromers containing adenosine and cannabinoid receptors are among those relevant to striatal function [ 65 – 71 ]. The occurrence of angiotensin receptors in the nigra and the striatum was followed by the identification of complexes formed by AT 1 R and AT 2 R [ 39 , 42 ]. In this paper, we showed that the Mas receptor forms heteroreceptor complexes with AT 1 R and AT 2 R and that such complexes are relevant for better understanding the role of RAS in neuroinflammation.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, MasR is key for microglia-driven development of the retinal vasculature [ 87 ]. The results presented here and those related to expression of AT 1 R-AT 2 R heteromers in striatal cells [ 42 ] suggest that MasR-related therapies to delay progression of PD should consider RAS components in microglia, with the ultimate goal of attenuating inflammation or skewing microglia toward the M2 neuroprotective phenotype [ 64 ]. RAS is well positioned to be targeted to polarization of microglia activated upon neuroinflammation [ 82 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations